THE EFFECTIVENESS OF USING GIST STRATEGY TOWARD STUDENTS' READING COMPREHENSION - Fauziyah, Rizkiyah Alifatul; Dari, Retno Wulan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
In reading activities, one of the abilities that must be mastered by students is reading comprehension in English. This research is motivated by the students' weak understanding of a reading text and the learning process still uses strategies that are less innovative and tend to be boring. Therefore, the researcher used the GIST (Generating Interaction between Schemata and Text) strategy to help improve students' reading comprehension through explanation text media. The aim of this study was to determine whether there was an improvement in students' reading comprehension after using the GIST strategy. The population of this study is eleventh grade students at Senior High School in Gresik while the sample from MAN 2 in Gresik which involved 36 students in class XI-2. This study used quantitative method with one group pretest-posttest design. Data collection used pre-test and post-test research instruments, then the data were analyzed using Paired T-test. The results of the study showed that the use of GIST strategy in the explanation text effectively helped students in understanding the reading well, it can be seen from the results of the mean pretest and posttest scores which increased significantly.